TISSUE INDICATORS AFFECTING TISSUE PROPERTIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Based on high-quality production of complex terry fabrics, of course, it is necessary to study the process from raw materials to the finished product and to determine the parameters that affect it. To do this, the effect of geometric and physicalmechanical properties of complex terry fabrics on its performance in the technological process was studied. The hygroscopicity, air and vapour permeability, electrification, optical and thermal storage properties of materials used in the group of geometric, physical properties of the fabric, as well as the tensile strength, elongation and deformation properties of the mechanical properties are determined and their effect on the weaving process studied.